Optimasi Algoritma Rate Adaptation Control CARA untuk Meningkatkan Throughput pada Wireless Mesh Network - Zahrul Maizi; Teuku Yuliar Arif; Nasaruddin Nasaruddin (Jurnal Serambi Engineering, 2021)
This paper examined throughput optimization issue in wireless mesh network (WMN), the weakest point of this network in regard to this matter.   A number of previous studies on this issue have been conducted, but most focus has been on general wireless network, only few studies so far have attempted on this network. This research aimed to optimize the CARA rate adaptation control algorithm in WMN network. The optimization was performed by adjusting the successtreshold and timeout parameters in the CARA algorithm to obtain an optimal throughput. The optimal result is showed that the optimal points of the success threshold and timeout are at range of 30-35. It is obviously seen in grid 4×5 and 5x5 where the throughput value of the optimization result continues to increase. Moreover, by adding the data transmission time for 100 seconds on grid 5×5 resulting the throughput value of 0.52206412 Mbps and after the optimization the throughput value increases up to 117% to 1.1350768 Mbps, when the success threshold and timeout value are 30. For an additional  150 seconds, the throughput value is 0.5074419333 Mbps and after the optimization the throughput increases up to 120% to 1.1211402 Mbps, when the success threshold and timeout value are 35.